High step-up DC-DC converter with switched capacitor-coupled inductor and voltage multiplier module - Subbulakshmy Ramamurthi; Palanisamy Ramasamy (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
A high step-up dc-dc converter based on a switched capacitor-coupled inductor (SC-CL) with voltage multiplier cells is proposed. It is composed of a SC-CL and a voltage multiplier module stacked on the load side. SC-CL produces the maximum output voltage with maximum voltage gain. These features make the projected converter suitable for renewable energy applications such as solar photovoltaic (PV). A low turn ratio of the coupled inductor is used for realizing the higher gain. It consists of a voltage boost unit SC-CL and a voltage multiplier module. In a DC micro-grid, PV energy is one of the utmost significant sources of power. Since the PV source voltage is very low, a very high voltage gain converter is required for a DC microgrid. Here, a step-up DC-DC converter topology with a very high voltage gain characteristic is proposed. The projected converter was simulated by MATLAB/Simulink to convert 30 V to 380 V.